Implikasi Konseptual Sila Kedua Pancasila Terhadap Harmoni Sosial - Joy Novi Yanti Lumbantobing; Yakobus Ndoda (International Forum of Researchers and Lecturers, 2024)
This research explores the conceptual implications of the Second Principle of Pancasila for social harmony in Indonesia. Pancasila, as the state's philosophical and ideological foundation, emphasizes the importance of